"Democracy and National Unity Day" in Turkey: the invention of a new national holiday. (15th May 2021) - Solomonovich, Nadav
Abstract: On the night of July 15, 2016, the Republic of Turkey experienced yet another military coup attempt. However, this attempt failed, mainly due to civilian protest and casualties. Their sacrifice, according to the Turkish state, led to the creation of a new national celebration in Turkey, the "Democracy and National Unity Day." Following the growing interest of historians in the field of national celebrations, this paper examines the creation of this holiday. It argues that the AKP government used this new holiday to shape the Turkish collective national memory and to introduce a national celebration that does not revolve around the founder of the Turkish Republic, Mustafa Kemal Atatürk, who symbolizes the secular camp in Turkey, but rather around the Justice and Development Party government and its more traditional and religious ideology, in the guise of celebrating Turkish democracy.